Evaluation of toxicity of ‘Vatsanabha’ (Aconitum ferox, Ranunculaceae) Before and After Shodhana - Deore, S.L. (2013)
Ayurvedic preparations contain toxic elements like heavy metals and other chemicals exceeding their permissible limits. Ayurvedic method of detoxification of such products involves Shodhana. Hence, in present paper it has been decided to replace Ayurvedic Shodhana process by chemical purification method and to study the benefits and/or drawbacks of the traditional Ayurvedic Shodhana process. Crude aconite root, Ayurvedic Shodhana treated aconite root and chemical Shodhana treated aconite root samples were evaluated for toxicity and changes by animal studies and thin layer chromatography (TLC) respectively. The results of the toxicity study suggest that the modified method of Shodhana is less efficient as compared to the traditional Ayurvedic Shodhana process. TLC studies have shown that pseudoaconitine and aconitine were converted into far less toxic substances like veratroyl pseudoaconine and benzoylaconine respectively only in traditional Ayurvedic Shodhana.